Effect of attachment type and implant position on the retention of mandibular implant-supported overdentures - Alireza Saadati; Farnaz Taghavi-Damghani; Sara Tavakolizadeh; Alireza Hadi (Journal of Dental Research, Dental Clinics, Dental Prospects)
Background. In implant-supported overdentures increase in the number of implants improves the retention and stability of the overdentures. A direct correlation exists between prosthesis retention and patient satisfaction. Therefore, this experimental study assessed the effect of attachment type and implant position on the retention of mandibular implant-supported overdentures. Methods. A transparent acrylic resin model of the mandible was fabricated, and dental implants were positioned at the first molar area (position 6), between the lateral incisor and canine teeth (positions B and D), and first premolars (positions A and E) bilaterally. Novaloc attachments (strong, medium, and light retentive caps) were used with ABDE, 6AE6, and 6BD6 implant positions. A Dolder bar attachment was also used with the ABDE implant position. Overdenture retention was measured under vertical loading, and the maximum dislodging force (MDF) was recorded. Data were analyzed by two-way and one-way ANOVA and post hoc Tukey tests (α=0.05). Results. The effects of attachment type and implant position [except for ABDE and 6AE6 with light retention insert (P=0.49), and 6AE6 and 6BD6 with strong retention insert (P=0.48)], and their interaction effect were significant on MDF (P<0.01). The highest retention was recorded for bar attachment (65.15 N), with the lowest for Novaloc attachment with light retention insert at ABDE implant position (11.97 N). Conclusion. With Novaloc attachments, minimum retention was recorded in ABDE, and maximum retention was recorded in the 6BD6 implant position due to the increased distance between attachments. The strong insert showed the highest retention value, which confirmed the manufacturer’s claim. Maximum retention was recorded with the bar and clip attachment.